2021
DOI: 10.21837/pm.v19i17.986
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Decision of Property Buyers: The Housing Quality, Financial Capabilities, and Government Policies Studies

Abstract: There are generally three types of house buyers called owner-occupiers, investors,and speculators. However, various factors that affect their decision to purchase a house. The research aims to identify the main factors that will affect the purchase decision of property buyers. Factors such as environmental factors, financial factors, governmental factors, subjective norms, and physical design factors will affect their decision to purchase. The research technique used is quantitative research. Descriptive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Further author stated that equilibrium of housing supply and demand will lead to affordable house price. Kenn, et al, (2021) done research about the house quality, financial capabilities, and government policies influence on the purchasing decision of a property consumers. That research concluded that environmental factor and subjective norm factor have positive influence as well as financial factor has a negative influence on the purchasing decision.…”
Section: Introductionmentioning
confidence: 99%
“…Further author stated that equilibrium of housing supply and demand will lead to affordable house price. Kenn, et al, (2021) done research about the house quality, financial capabilities, and government policies influence on the purchasing decision of a property consumers. That research concluded that environmental factor and subjective norm factor have positive influence as well as financial factor has a negative influence on the purchasing decision.…”
Section: Introductionmentioning
confidence: 99%